Optical microfluidic waveguides and solution lasers of colloidal semiconductor quantum wells - Maskoun, Joudi (2021)
The realization of high-quality lasers in microfluidic devices is crucial for numerous applications, including biological and chemical sensors and flow cytometry, and the development of advanced lab-on-chip (LOC) devices. Herein, an ultralow-threshold microfluidic single-mode laser is proposed and demonstrated using an on-chip cavity. CdSe/CdS@Cdx Zn1-x S core/crown@gradient-alloyed shell colloidal semiconductor quantum wells (CQWs) dispersed in toluene are employed in the cavity created inside a poly(dimethylsiloxane) (PDMS) microfluidic device using SiO2 -protected Ag mirrors to achieve in-solution lasing. Lasing from such a microfluidic device having CQWs solution as a microfluidic gain medium is shown for the first time with a record-low optical gain threshold of 17.1 µJ cm- ² and lasing threshold of 68.4 µJ cm- ² among all solution-based lasing demonstrations. In addition, air-stable SiO2 protected Ag films are used and designed to form highly tunable and reflective mirrors required to attain a high-quality Fabry-Pérot cavity. These realized record-low thresholds emanate from the high-quality on-chip cavity together with the core/crown@gradient-alloyed shell CQWs having giant gain cross-section and slow Auger rates. This microfabricated CQW laser provides a compact and inexpensive coherent light source for microfluidics and integrated optics covering the visible spectral region.